Understanding employer engagement in youth labour market policy in the UK. (21st November 2017) - Simms, Melanie
Abstract : This article applies van Gestel and Nyberg's framework to analyse employers' decisions about whether to engage in policies to help young people into work. The article identifies two main logics underpinning organisational decision making: an HR logic and a corporate social responsibility (CSR) logic. It is argued that engaged employers see a clear alignment in those logics, whereas less engaged employers see few advantages in one, the other or both areas. When this analysis is located within an institutional context that accounts for the agency of key actors, it is argued these logics explain decisions about whether or not to engage with particular labour market policies.